2022
DOI: 10.25259/sni_747_2022
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy versus ventriculoperitoneal shunt insertion for the management of pediatric hydrocephalus in African centers – A systematic review and meta-analysis

Abstract: Background: Ventriculoperitoneal shunt (VPS) insertion and endoscopic third ventriculostomy (ETV) are common surgical procedures used to treat pediatric hydrocephalus. There have been numerous studies comparing ETV and VPS, but none from an African perspective. In this study, we sought to compare outcomes from African neurosurgical centers and review the associated complications. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses were used in conducting this study. PubMed, Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In summary, our study’s findings align with those of previous research in the field. A Jesuyajolu et al study [ 16 ] similarly observed no significant difference between VPS and ETV treatments, although they noted a slightly higher mortality risk of 0.05% in VPS compared to 0.01%. Sheik et al study [ 17 ], which involved 100 patients treated with either VPS or ETV, suggested that VPS might carry a higher risk of long-term complications.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, our study’s findings align with those of previous research in the field. A Jesuyajolu et al study [ 16 ] similarly observed no significant difference between VPS and ETV treatments, although they noted a slightly higher mortality risk of 0.05% in VPS compared to 0.01%. Sheik et al study [ 17 ], which involved 100 patients treated with either VPS or ETV, suggested that VPS might carry a higher risk of long-term complications.…”
Section: Discussionmentioning
confidence: 98%
“…ETV was associated with a statistically significant lower risk of procedure-related infection compared to shunt [21]. It is generally accepted that true differences exist regarding complication rates among centers or among individual neurosurgeons, according to their personal experience [59,65,66].…”
Section: Tve/vp Shunt Comparisonmentioning
confidence: 97%
“…Recent comparisons between these interventions in adult and pediatric populations have shown that ETV has lower complication rates, particularly in postoperative infections and hematomas, although no differences were noted in mortality or postoperative success rates. 7,8 In pregnant patients, ETV appears to offer several advantages over shunt placement. First, it eliminates the need for foreign body implantation, reducing the risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…ETV offers an alternative CSF flow pathway, establishing communication between the third ventricle and adjacent compartments near the brainstem. 6 7 8 This procedure demands precision in identifying anatomical landmarks such as the foramen of Monro and the basilar artery to prevent complications such as hemorrhage and neurological injury. Moreover, factors such as ventricular thickening or scarring may impede stoma creation and diminish ETV success rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation